An aggregated understanding of cellulase adsorption and hydrolysis for ball-milled cellulose. (February 2019) - Lu, Minsheng; Li, Junbao; Han, Lujia; Xiao, Weihua
Graphical abstract: Highlights: Hydrophobicity and surface charge are the key factors affecting cellulase adsorption. Specific surface area and crystallinity are the key factors affecting glucose yield. Ball milling can greatly reduce the enzyme use. Increasing enzyme binding is not necessary for higher initial hydrolysis rate. Abstract: This study evaluated the effects of physicochemical properties of a series of ball-milled cellulose on cellulase adsorption and glucose yield. The relationship between cellulase adsorption and initial hydrolysis rate was also discussed. We found that hydrophobicity and surface charge are the key factors affecting cellulase adsorption on ball-milled cellulose. The results demonstrated that glucose yield had a positive correlation with specific surface area, while showed a negative correlation with particle size, degree of polymerization and crystallinity. Among these properties, specific surface area and crystallinity are the key factors affecting glucose yield. As ball milling progressed, cellulose showed lower enzyme adsorption capacity/amount of bound enzyme during initial stage of hydrolysis, but had higher initial hydrolysis rate. The enhanced rate is attributed to the fact that the amorphous region produced by ball milling reduces the free energy required for decrystallization thus increases the catalytic efficiency of the bound enzyme.